BIOCERAMICS IN ORAL REHABILITATION - A PUTATIVE HOPE FOR SAVING THE TEETH WITH VERTICAL ROOT FRACTURE - Alexandru Andrei Iliescu; Kamel Earar; Anamaria Zaharescu; Alina Ramona Dimofte; Paula Perlea; Madalina Matei; Andrei Iliescu (Romanian Society of Oral Rehabilitation, 2020)
Vertical root fracture involves mostly the endodontically treated teeth being extended from the root canal to the periodontal ligament typically in bucco-lingual plan. Its common efficient treatment is the whole tooth extraction and sometomes root resection or hemisection. As the prevention of vertical root fracture endodontically treated teeth is the best choice it is mandatory to avoid an excessive loss of tooth structure by preparing the access cavity and enlargement of root canals. Aiming long-term clinical success presently the key goal is to strengthen the structure of these teeth. The use of these newcomers, bioceramic sealers in root canal fillings, would be advantageous over time as it result in a monoblock sealer/gutta-percha cone/dentin able to increase the mechanical resistance of the tooth root.